Augmented reality in biology education: A systematic literature review - Tutut Indria Permana; H. Husamah; Moh Irfan Nurhamdani; Alia Zaskia; Aulia Savitri; Diva Aulia Salsabila (Universitas Muhammadiyah Malang, 2024)
Augmented Reality (AR) has seen extensive utilization in the modern era, driven by rapid technological advancements. The aim of the Systematic Literature Review (SLR) method is to meticulously analyze and assess previous research on a specific phenomenon in a systematic and explicit manner. The search was conducted on the Scopus database using the keyword